2019
DOI: 10.1007/s10461-019-02545-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Training and Correlates of Knowledge, HIV Screening and Prescribing of nPEP and PrEP Among Primary Care Providers in Southeast United States, 2017

Abstract: The Southeast accounted for most HIV diagnoses (52%) in the United States in 2015. Primary care providers (PCPs) play a vital role in HIV prevention for at-risk persons and treatment of persons living with HIV. We studied HIV-related training, knowledge, and clinical practices among PCPs in the Southeast to address knowledge gaps to inform HIV prevention strategies. Between April and August 2017, we conducted an on-line survey of a representative sample of PCPs in six Southeast jurisdictions with high rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Recent studies have identified gaps in provider knowledge of HIV-related services, and in the actual provision of those HIV-related services to women [36,37]. Thus, provider knowledge has been a focal point of HIV prevention and treatment interventions, with demonstrated success in improving outcomes along the HIV prevention and treatment care continuum [37,38]. Beyond HIV-specific medical education, training and development in structural competency may be particularly salient for medical professionals who serve Black and Latina WLWH because such trainings show promise in preparing providers to address aspects of the distinct and overlapping social and institutional barriers to health experienced by WLWH [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified gaps in provider knowledge of HIV-related services, and in the actual provision of those HIV-related services to women [36,37]. Thus, provider knowledge has been a focal point of HIV prevention and treatment interventions, with demonstrated success in improving outcomes along the HIV prevention and treatment care continuum [37,38]. Beyond HIV-specific medical education, training and development in structural competency may be particularly salient for medical professionals who serve Black and Latina WLWH because such trainings show promise in preparing providers to address aspects of the distinct and overlapping social and institutional barriers to health experienced by WLWH [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the important function that simply having a primary care provider has in access to basic healthcare like HIV testing. 11 12 Meanwhile, those with HIV-positive results, regardless of how recent their previous HIV test was prior to enrollment, differed from those with negative results in many ways that are known to be associated with HIV risk. These included racial and income disparities, housing instability, recent transactional sex, and perhaps most notably, recent methamphetamine use.…”
Section: Discussionmentioning
confidence: 99%
“…HIV medical care providers play an indispensable role in nPEP uptake, especially medication prescription [17]. Previous surveys have reported on HIV care providers prescribing nPEP in developed countries [18][19][20][21][22][23], most often including factors such as practice specialty, the number of persons living with HIV in treatment, provider familiarity with nPEP, and the nPEP guideline in place [18,19,23]. As these surveys were conducted in developed countries with nPEP guidelines, it is uncertain whether the situation is similar in developing countries without nPEP guidelines.…”
Section: Previous Studies and Existing Gapmentioning
confidence: 99%